"I can't come to the words": Effects of including military flavour when testing the oral proficiency of Norwegian joint terminal attack controllers. (October 2022) - Grande, Birgitte; Leishman, Clayton D.; Skilleås, Hege Kristine
Abstract: Joint Terminal Attack Controllers (JTACs) direct close-air-support during NATO operations, however, non-native speaker JTACs struggle to meet the NATO English proficiency requirement. This paper examines the effects of including more "military flavour" (Green & Wall, 2005) in the oral proficiency interview (OPI) for JTACs, developed in accordance with NATO Standardisation Agreement (STANAG) 6001. The new test format, called the "OPI+" included linguistic tasks associating military content domains with the linguistic functions traditionally elicited in the OPI, allowing for comparisons to be made between the two. The test was tried on the Norwegian JTAC selection course ( N = 25). Test-taker performance was holistically rated in accordance with STANAG 6001, and candidate output on four OPI+ tasks later transcribed and analysed using discourse analytic measures. Findings suggest that while adding more professional flavour to the test of speaking will improve face validity, test-takers' qualitative and quantitative performance will not be significantly affected, as long as the language functions elicited remain the same. Moreover, when it comes to testing the professional language JTACs need in the target language use situation, the standard STANAG 6001 OPI test format apparently leaves something to be desired. Highlights: Effects of including military content in an oral proficiency interview were measured. Discourse analytic measures were performed in addition to holistic ratings. A general proficiency rating scale was used. Inclusion of professional, domain-specific content increased face validity. Professional, domain-specific content did not improve qualitative performance.